2020
DOI: 10.1140/epjc/s10052-020-08568-6
|View full text |Cite
|
Sign up to set email alerts
|

A note on the total action of 4D Gauss–Bonnet theory

Abstract: Recently, a novel four-dimensional Gauss–Bonnet theory has been suggested as a limiting case of the original D-dimensional theory with singular Gauss–Bonnet coupling constant $$\alpha \rightarrow \alpha /(D-4)$$ α → α / ( D - 4 ) . The theory is proposed at the level of field equations. Here we analyse this theory at the level of action. We find that the on-shell action and surface terms split into parts, one of which does not scale like $$(D-4)$$ ( D - 4 ) . The limiting $$D\rightarrow 4$$ D → 4 proced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 34 publications
2
66
0
Order By: Relevance
“…However, the original claim of ref. [37] is clearly in contradiction with the Lovelock theorem, and some subtleties and criticisms on the D → 4 limit were revealed in [87][88][89][90][91], concluding that there is no pure four-dimensional Einstein-Gauss-Bonnet gravity [92,93]. In refs.…”
Section: Jhep12(2020)192mentioning
confidence: 99%
“…However, the original claim of ref. [37] is clearly in contradiction with the Lovelock theorem, and some subtleties and criticisms on the D → 4 limit were revealed in [87][88][89][90][91], concluding that there is no pure four-dimensional Einstein-Gauss-Bonnet gravity [92,93]. In refs.…”
Section: Jhep12(2020)192mentioning
confidence: 99%
“…This processing method in [41] has led to a great deal of discussion, see e.g. [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also some debates on whether the novel gravity is a consistent and well-defined theory in four dimensions [45][46][47][48][49][50][51][52][53]. Such as, Gurses et al pointed out that the novel 4D EGB gravity does not admit a description in terms of a covariantly-conserved rank-2 tensor in four dimensions and the dimensional regularization procedure is ill-defined, since one part of the GB tensor, the Lanczos-Bach tensor, always remains higher dimensional [46].…”
Section: Introductionmentioning
confidence: 99%
“…So generally speaking, the theory only makes sense on some selected highly-symmetric spacetimes, such as the FLRW spacetime and static spherically symmetric spacetime. Mahapatra found that in the limiting D → 4 procedure, the theory gives unphysical divergences in the on-shell action and surface terms in four dimensions [47]. Shu showed that at least the vacuum of the theory is either unphysical or unstable, or has no well-defined limit as D → 4 [48].…”
Section: Introductionmentioning
confidence: 99%